An overview of biological control of plant disease in Afghanistan - Fazel Rab Aria; Fraidoon Karimi; Mohammad Yousuf Fakoor; Ghulam Rasul Faizi; Xianchao Sun (Biological Control)
In Afghanistan, there exists an urgent necessity for efficacious, environmentally sustainable plant disease management strategies, as chemical pesticides and conventional methods have long been prevalent in the country. Biological control utilizing agents such as Trichoderma species and viral biopesticides is emerging as a promising alternative. Agriculture, a primary source of income in rural areas, would benefit substantially from the adoption of sustainable methods. Recent initiatives, including the National Horticulture and Livestock Project (NHLP), have established laboratories and production facilities to promote the utilization of biocontrol agents. These agents offer a more benign alternative to chemical pesticides, mitigating health risks. However, challenges persist in the large-scale production, storage, and distribution of biocontrol agents. To ensure the successful integration of biological control, collaboration among researchers, extension agencies, and agriculturalists is essential. Ongoing research, infrastructure enhancements, and education are crucial for overcoming these challenges and fostering the widespread adoption of biological control techniques. By addressing these barriers, Afghanistan can progress towards more sustainable agricultural practices, employing biological control as a responsible method for managing plant diseases.